2009
DOI: 10.1021/jp806411c
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of NaNO3 in Water: Diffraction and Molecular Dynamics Simulation Study

Abstract: The structure of a series of aqueous sodium nitrate solutions (1.9-7.6 M) was studied using a combination of experimental and theoretical methods. The results obtained from diffraction (X-ray, neutron) and molecular dynamics simulation have been compared and the capabilities and limitations of the methods in describing solution structure are discussed. For the solutions studied, diffraction methods were found to perform very well in description of hydration spheres of the sodium ion but do not yield detailed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 69 publications
11
37
0
Order By: Relevance
“…Pair correlation functions, energies and other structural quantities were calculated for the model systems, and we found a satisfactory agreement with the structural information derived from x-ray and from neutron diffraction measurements for the real solutions [22]. In addition to the correlation functions 43006-2 presented in [22] here we show our results for the ion-ion correlations from MD and MC simulations for six solutions of different concentrations. In the case of molecular ions, we consider every atom of the NO ¿ -ion to be one site with a partial charge.…”
Section: Computer Simulationssupporting
confidence: 73%
See 2 more Smart Citations
“…Pair correlation functions, energies and other structural quantities were calculated for the model systems, and we found a satisfactory agreement with the structural information derived from x-ray and from neutron diffraction measurements for the real solutions [22]. In addition to the correlation functions 43006-2 presented in [22] here we show our results for the ion-ion correlations from MD and MC simulations for six solutions of different concentrations. In the case of molecular ions, we consider every atom of the NO ¿ -ion to be one site with a partial charge.…”
Section: Computer Simulationssupporting
confidence: 73%
“…For the nitrate ion we used the values given in [22]. In addition to the MD simulations for the four solutions studied in [22] we have also performed MD and MC simulations of aqueous sodium nitrate solutions with concentrations of ¼º mol dm ¿ [24] and of º mol dm ¿ [25]. Pair correlation functions, energies and other structural quantities were calculated for the model systems, and we found a satisfactory agreement with the structural information derived from x-ray and from neutron diffraction measurements for the real solutions [22].…”
Section: Computer Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…has been characterized as exhibiting mild interactions with water, i.e., weakly hydrated as a result of its small charge and relatively large effective ionic that induce limited distortion of the hydrogen bonding of the surrounding water [172][173] . These features might have contributed to the large disparity in the reported water coordination of the nitrate anion from different experimental sources, including NMR [174][175][176][177][178][179][180] , IR [181][182][183][184][185][186][187] , Raman [173][174][188][189][190][191][192][193][194][195][196][197] , XRD 172-173, 190, 193, 195-204 , as well as NDIS [205][206][207][208][209][210] , and point to unresolved concerns regarding the determination and interpretation of the hydration microstructure of nitrates in a variety of aqueous environments 63 .…”
mentioning
confidence: 99%
“…Structural methods such as neutron diffraction (ND) and X-ray diffraction have contributed to the characterization of hydration and ion pairing effects in NaNO 3 and other alkaline nitrates solutions. 48 A more recent neutron diffraction with isotopic substitution measurement and molecular dynamics (MD) simulation were both applied to study CsNO 3 and Cs 2 CO 3 in solution and showed that both hydration and ion pairing are weak for nitrate compared with carbonate. Simulations of nitrate water interactions on microhydrated NO3 - were carried out on discreet NO3 - H 2 O clusters with one to eight water molecules and theoretical IR spectra were given.…”
Section: Introductionmentioning
confidence: 99%